Metastatic testicular choriocarcinoma presenting as eyelid swelling and ptosis. (4th July 2022) - Sivagnanasithiyar, Tharsica; Okafor, Linda; Faust, Guy; Mudhar, Hardeep Singh; Sii, Samantha; Knapp, Christopher; Sampath, Raghavan
ABSTRACT: A 34-year-old man presented with an 8-day history of swelling and ptosis affecting the right upper eyelid. An MRI scan showed right superior rectus enlargement. Histology of an incisional biopsy of the muscle demonstrated metastatic choriocarcinoma to the orbit, positive for pan-cytokeratins, beta-HCG and GATA3. Possible primary sites included testis. An ultrasound of the testes identified bilateral testicular masses, highly suspicious for primary testicular malignancy. A CT scan of the chest, abdomen and pelvis identified disseminated metastatic disease conferring a poor prognostic germ cell tumour. The overall interpretation was of disseminated testicular choriocarcinoma and the patient is currently undergoing intensive chemotherapy.